P-B35 Design of a broadly neutralizing human rhinovirus antigen. (January 2016) - Wiggins, T; Lee, W-M; Bushnell, RV; Tobin, JK; Turner, RB; Nara, PN; Tobin, GJ
Abstract : The 150+ serotypes of Human rhinoviruses (HRV) cause the majority of the common colds. Although the disease is relatively mild for most of those infected, infection with HRV can exacerbate asthma and COPD and result in hospitalizations or death. Infection with one serotype stimulates serotype-restricted humoral immunity that is thought to protect from re- infection at neutralization titers as low as 1:2. However, little, if any, cross- serotype immunity is developed and the individual is open to infection by any of the other serotypes. Using a multi-pronged approach that included analysis of escape mutants, evolution in experimentally infected humans, studies of divergent sequences, and analysis of structural data, we designed a series of antigenic variants using our Immune Refocusing Technology (IRT). Five IRT mutants, each having amino acid substitutions in one epitope only, were reverse engineered into recombinant HRV16 and into baculovirus- expressed HRV39 VLPs. As expected, rabbits immunized with unmodified HRV16 or HRV39 antigens developed neutralizing antibodies restricted to the parental antigen. However, sera from rabbits immunized with the IRT antigens cross-neutralized numerous serotypes. The leading candidate, 39M5, stimulated antibodies that neutralized 40 of the 61 serotypes tested. The data demonstrate the power of the Immune Refocusing Technology in the design of broadly protective antigens and encourage the further development of HRV IRT antigens as vaccine candidates.